Budd‐Chiari syndrome on background of JAK2V617F mutation with no hematologic abnormalities - Ammara Bint I Bilal (14777176) (2023)
Whenever considering idiopathic Budd-Chiari syndrome, consider the possibility of JAK2 mutation even if clinical parameters are within normal range. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4668